2019
DOI: 10.1253/circj.cj-18-1044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Therapeutic Angiogenesis Using Autologous Bone Marrow-Derived Mononuclear Cells Implantation in Critical Limb Ischemia With Scleroderma ― Subanalysis of the Long-Term Clinical Outcomes Survey ―

Abstract: CD, particularly with systemic sclerosis (SSc, scleroderma) have experienced Raynaud's phenomenon or digital ulcers (DU) because of inadequate peripheral blood supply. Intractable ischemic ulcers negatively affect patients' quality of life (QOL), and may lead to limb amputation. 2 The European League against Rheumatism (EULAR) recommends intravenous (IV) iloprost, PDE-5 inhibitors, and C ritical limb ischemia (CLI) is caused by chronic arterial obstruction, mainly caused by arteriosclerosis obliterans (ASO), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…9). 30) These results suggest that the BM-MNC implantation is safe and effective in patients with no-option CLI. In particular, the BM-MNC implantation is effective at alleviating ischemic symptoms in patients with TAO and CD.…”
Section: Results In Patients With Aso and Taomentioning
confidence: 74%
See 1 more Smart Citation
“…9). 30) These results suggest that the BM-MNC implantation is safe and effective in patients with no-option CLI. In particular, the BM-MNC implantation is effective at alleviating ischemic symptoms in patients with TAO and CD.…”
Section: Results In Patients With Aso and Taomentioning
confidence: 74%
“…7). 30,31) In this study, patients with CD were divided into scleroderma (SSc) and non-SSc groups according to the immunological mechanism for each disease. The SSc group included some SScrelated diseases (SSc; calcinosis, Raynaud s phenomenon, esophageal dysmotility, sclerodactyly, and telangiectasia; and mixed connective tissue disease).…”
Section: Results In Patients With Aso and Taomentioning
confidence: 99%
“…As the results of therapeutic angiogenesis using autologous BM-MNCs in 69 patients (39 SSc, 30 other collagen diseases) with severe ischemic limb caused by collagen disease accumulated in the TACT study, the 10-year overall survival rate, major amputation-free rate, and amputation-free survival rate were 67.6, 90.9, and 61.2%, respectively with the adverse events occurred in 8.7% (101). The 10-year major amputation-free rates were 97.4% in the SSc group and 82.6% in the other collagen disease group, and the rate of limb salvage tended particularly to be higher in the SSc group among the collagen diseases (102).…”
Section: Therapeutic Angiogenesis Using Vascular Endothelial Progenitor Cellsmentioning
confidence: 89%
“…Many clinical trials, such as the Japan Trial for Therapeutic Angiogenesis using Cell Transplantation, have reported on the safety and efficacy of therapeutic angiogenesis using autologous bone marrow-derived mononuclear cell (BM-MNC) implantation in patients with no-option CLTI, particularly that caused by TAO. [12][13][14][15][16][17] In the future, BM-MNCs will need to be widely commercialized to improve the limb salvage rate of patients with CLTI caused by TAO. Thus, we designed a clinical trial to further evaluate the efficacy of BM-MNC implantation.…”
Section: Participantsmentioning
confidence: 99%